Evaluation of Anatomical Variations of Mandibular Canal through Cone Beam Computed Tomography - Shirin Pazhuhandeh; Hasan Momeni; Shahab Etemadi; Arman Ebrahimi (Isfahan University of Medical Sciences, 2021)
The inferior alveolar canal is an important anatomical structure in the field of dentistry implants and cone beam computed tomography (CBCT) is an important diagnostic technique. The aim of this study was to evaluate the prevalence of anatomical variations of the mandibular canal observed in CBCT images.Materials & Methods:In this descriptive-analytic study 384 inferior alveolar canals were evaluated in 192 patients, who were referred to the radiology department of Isfahan Azad University in 1396 for a cone-beam computed tomography. Radiographs were performed to assess the frequency of different left and right mandibular canal segregations by sex in terms of upper and lower position, baccolingual position, shape of the general canal. The frequency and different types of existing mandibular plug canals were also evaluated. Data were analyzed by Chi Square, independent T Test, paired t-test. (p value < 0.05).Results:The mandibular canal was 2.1% of the lower position, 11.9% of the upper position and 86% of the middle position. Statistically significant differences were observed between the frequency distributions of canal positions and gender (p value = 0.004). The prevalence of Bifid mandibular canals was 14.8%. There was no significant relationship between the shape of the general channel path and gender. There was no significant difference between the mean distance between the mandibular canal and the buccal cortex in both Molar and Ramus with the sex of the subjects and the side of the canal (p value < 0.05).Conclusion:The highest frequency of mandibular canal in most subjects was on the right in the intermediate position. The mean distance between mandibular canal and buccal cortex in Ramos and Molars area on both right and left sides was not significantly different between men and women